Evaluation of a deterministic grid-based Boltzmann solver (GBBS) for voxel-level absorbed dose calculations in nuclear medicine. (25th May 2016) - Mikell, Justin; Cheenu Kappadath, S; Wareing, Todd; Erwin, William D; Titt, Uwe; Mourtada, Firas
Abstract: To evaluate the 3D Grid-based Boltzmann Solver (GBBS) codeATTILA ® for coupled electron and photon transport in the nuclear medicine energy regime for electron (beta, Auger and internal conversion electrons) and photon (gamma, x-ray) sources. Codes rewritten based onATTILA are used clinically for both high-energy photon teletherapy and 192 Ir sealed source brachytherapy; little information exists for using the GBBS to calculate voxel-level absorbed doses in nuclear medicine. We compared DOSXYZnrc Monte Carlo (MC) with published voxel- S -values to establish MC as truth. GBBS was investigated for mono-energetic 1.0, 0.1, and 0.01 MeV electron and photon sources as well as 131 I and 90 Y radionuclides. We investigated convergence of GBBS by analyzing different meshes ( M 0, M 1, M 2 ), energy group structures ( E 0, E 1, E 2 ) for each radionuclide component, angular quadrature orders ( S 4, S 8, S 16 ), and scattering order expansions ( P 0 – P 6 ); higher indices imply finer discretization. We compared GBBS to MC in (1) voxel- S -value geometry for soft tissue, lung, and bone, and (2) a source at the interface between combinations of lung, soft tissue, and bone. Excluding Auger and conversion electrons, MC agreed within ≈5% of published source voxel absorbed doses. For the finest discretization, most GBBS absorbed doses in the source voxel changed by less than 1% compared to the next finest discretization along each phase space variable indicating sufficient convergence. For the finest discretization, agreement with MC in the source voxel ranged from −3% to −20% with larger differences at lower energies (−3% for 1 MeV electron in lung to −20% for 0.01 MeV photon in bone); similar agreement was found for the interface geometries. Differences between GBBS and MC in the source voxel for 90 Y and 131 I were −6%. The GBBS ATTILA was benchmarked against MC in the nuclear medicine regime. GBBS can be a viable alternative to MC for voxel-level absorbed doses in nuclear medicine. However, reconciliation of the differences between GBBS and MC at lower energies requires further investigation of energy deposition cross-sections.